Thucydides - Rhodes, P. J. (Ancients in Action Ser, 2015)
FC -- Half title -- Ancients in Action -- Title -- Copyright -- Contents -- Preface -- References to Ancient Texts -- Principal Dates -- Map: The World of Thucydides -- 1 The World of Thucydides -- 2 Thucydides the Historian -- 3 Thucydides the Thinker -- 4 After Thucydides -- Further Reading -- Index.